Sinón como personaje en el teatro español del Siglo de Oro - Echavarren, Arturo (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
This paper focuses on the pervivence of Sinon in Spanish Golden Age drama as a character. After a commentary on Greek and Latin Literature sources to the myth, this character is analysed in five plays: La destrucción de Troya (1647), «entremés» wrongly attributed to Góngora, La destrucción de Troya (XVIIth century), by Cristóbal de Monroy, wherein Sinon is the gracioso of the play, Troya abrasada (ca. 1640), by Calderón de la Barca y Zabaleta, wherein Sinon is a tragic traitor, El robo de Elena y destrucción de Troya (XVIIth century), sacramental play by Rojas Zorrilla wherein Sinon is an allegory of Godly Love, and Los amores de Dido y Eneas (XVIIth century), by Cristóbal de Morales, wherein Sinon is a remnant of the Renaissance Theatre prologue. Aquotation from a fictitious play called Astucias de Sinón, in El Diablo cojuelo (1641), by Vélez de Guevara, is also analysed.